Intention to Buy Halal Cosmetic Products by Young Adult Muslim - Iriani, Sri Setyo; Sanaji, Sanaji; Sayuti, Nazura Mohamed; Arshad, Azlin Syafinaz (Jurnal Manajemen Bisnis, 2024)
Research aims: This paper aims to determine and analyze the influence of personal attitudes, subjective norms, and perceptions of controlling behavior of young adult Muslims on purchase intention of halal cosmetic products and factors that have the most significant influence on purchase intentionDesign/Methodology/Approach: The research approach is quantitative, the population in this study is an infinite number of Indonesian young adult Muslim women, using convenience and purposive sampling as a sampling technique with 120 respondents. Data collection technique using an online questionnaire via Google formResearch findings: This research found that subjective norms and perceived behavioral control influence purchase intention on halal cosmetic products among young adult Muslim women. This research also found that personal attitude did not influence the purchase intention of halal cosmetic products among young adult Muslim women.Theoretical Contribution/Originality: This study explores awareness about halal cosmetic products in addition to contributing to the literaturePractitioners/Policy Implications: This research implies that cosmetic manufacturers need to apply a halal label to their cosmetics to enter the market of young adult Muslim womenResearch Limitations/Implications: This study has several limitations, including the dissemination of online questionnaires has not been able to capture respondents optimally; and have not been able to do in-depth interviews to explore why the variable has an effect or not